PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN INDEKS IDX HIGH DIVIDEND 20 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2017 - A.A. Ade Eka Putra Andryawan; I Wayan Sukadana; I Wayan Widnyana (VALUES, 2021)
This study aimed to determine the effect of Profitability on Dividend Policy, Liquidity on Dividend Policy, 3) Leverage on Dividend Policy. The location of this research is on the Indonesia Stock Exchange (IDX) by accessing the official website of the IDX, namely www.idx.co.id. The population in this study were 20 index companies of IDX High Dividend 20 listed on the Indonesia Stock Exchange on 2015-2017. The sample analysis technique used was purposive sampling technique, namely 20 companies with a total of 60 observations. The data analysis technique used is multiple linear regression analysis. The test results show that profitability a positive and significant effect on dividend policy in the index companies of IDX High Dividend 20. Liquidity has no effect on dividend policy in index companies of IDX High Dividend 20 and Leverage has a negative and significant effect on dividend policy in index companies of IDX High Dividend 20. Profitability, Liquidity, and Leverage simultaneously affect dividend policy in index companies of IDX High Dividend 20.